2012
DOI: 10.1158/1535-7163.mct-11-1044
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Homologous Recombination and Abnormal Cell-Cycle Progression in Radioresistance of Glioma-Initiating Cells

Abstract: Glioblastoma multiforme (GBM) is the most common form of brain tumor with a poor prognosis and resistance to radiotherapy. Recent evidence suggests that glioma-initiating cells play a central role in radioresistance through DNA damage checkpoint activation and enhanced DNA repair. To investigate this in more detail, we compared the DNA damage response in nontumor forming neural progenitor cells (NPC) and glioma-initiating cells isolated from GBM patient specimens. As observed for GBM tumors, initial characteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 44 publications
2
53
0
3
Order By: Relevance
“…In another report, although CD133+ glioma stem cells were shown to display elongated cell cycle and enhanced basal activation of Chk1 and Chk2, neither BER nor SSB repair was found to be increased in CD133+ compared to CD133-glioma cells [45] . Interestingly, Lim et al [46] reported a more efficient HR repair in GICs, but neither a extended cell cycle nor augmented activation of checkpoint proteins was observed in these cells. The reduced DDR was also reported in other CSCs.…”
Section: Activation Of Cell Cycle Checkpoint Machinerymentioning
confidence: 95%
“…In another report, although CD133+ glioma stem cells were shown to display elongated cell cycle and enhanced basal activation of Chk1 and Chk2, neither BER nor SSB repair was found to be increased in CD133+ compared to CD133-glioma cells [45] . Interestingly, Lim et al [46] reported a more efficient HR repair in GICs, but neither a extended cell cycle nor augmented activation of checkpoint proteins was observed in these cells. The reduced DDR was also reported in other CSCs.…”
Section: Activation Of Cell Cycle Checkpoint Machinerymentioning
confidence: 95%
“…Recent studies have extensively investigated the cellular and genetic mechanisms underlying glioblastoma progression (4,5). Although the molecular mechanisms underlying glioma radioresistance have yet to be elucidated, they are thought to involve dysregulated gene expression (6).…”
Section: Introductionmentioning
confidence: 99%
“…In metastatic brain tumors,the expression levels of phosphorylatedChk1 proteins tend to be higher in radioresistant cancer than in radiosensitive cell lines (Seol et al, 2011). Lim et al have proved that cell-cycle checkpoint abnormalities may contribute to the radioresistance of glioma-initiating cells and may be suitable targets for therapy (Lim et al, 2012). The cell cycle division cycle 25 (Cdc25) protein phosphates, including three family proteins, Cdc25a, Cdc25b, Cdc25c, are critical components of cell engine that function to drive cell cycle transitions by dephosphorylating and activating cyclin-dependent kinases (Cdks) (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%